School selectivity, peers, and mental health - Aline Bütikofer; Rita Ginja; Fanny Landaud; Katrine V. Løken (Institute for Fiscal Studies (IFS), 2021)
Although many students suffer from anxiety and depression, and often identify school pressure and concerns about their futures as the main reasons for their worries, little is known about the consequences of a selective school environment on students' mental health. Using a regression discontinuity analysis in the largest Norwegian cities, we show that eligibility to enroll in a more selective high school increases the probability of enrollment in higher education and decreases the probability of diagnosis or treatment of psychological problems. We provide suggestive evidence that changes in both teacher and peers' characteristics are likely drivers of these effects.
Keywords: I12; I21; I24; 330; Health; school inputs; selective education